2015
DOI: 10.1016/j.vaccine.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Individual level determinants for not receiving immunization, receiving immunization with delay, and being severely underimmunized among rural western Kenyan children

Abstract: Immunization coverage among 12-23 month old children was high, yet a substantial proportion of children were vaccinated with delay. Although vaccine coverage and timeliness are often conceptualized as separate measures, the finding that delayed pentavalent1 receipt was a strong risk factor for not receiving future immunizations indicates the two measures are intertwined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 38 publications
3
23
1
Order By: Relevance
“…Second, this trial was designed and implemented to closely mimic an effectiveness study and with scalability in mind by enrolling caregivers independent of mobile phone ownership, a study design unlike some m-health intervention trials that provide a mobile phone 7 or require one for enrolment 8, 14, 37. We do not believe the high coverage estimates observed in the control group were due to study participation (ie, Hawthorne effect) because the coverage was similar to that in a baseline survey done before the trial 27 . Moreover, we sought to minimally interfere with participants' care-seeking behaviours because household visits were only done at enrolment and 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, this trial was designed and implemented to closely mimic an effectiveness study and with scalability in mind by enrolling caregivers independent of mobile phone ownership, a study design unlike some m-health intervention trials that provide a mobile phone 7 or require one for enrolment 8, 14, 37. We do not believe the high coverage estimates observed in the control group were due to study participation (ie, Hawthorne effect) because the coverage was similar to that in a baseline survey done before the trial 27 . Moreover, we sought to minimally interfere with participants' care-seeking behaviours because household visits were only done at enrolment and 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This rural study area has high baseline immunisation levels, moderate levels of mobile phone ownership, 27 and a widespread mobile-money network 22 . Replicating this trial in settings where mobile phone ownership is lower and mobile-money systems are absent or less frequently used might not be possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of the BCG and polio vaccines timely may stimulate children’s immune systems, which may lead to a decrease in mortality as a result of other infectious diseases. In previous studies, delays in the first polio and DTP vaccinations led to delays in the second and third vaccinations in the series, which indicated that these children remained vulnerable to vaccine-preventable diseases 7 20 34 38. Unfortunately, there has been no study to examine the factors influencing delays in BCG and OPV vaccinations in Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies in sub-Saharan Africa, we found that children whose primary caregiver had completed secondary education were less likely to have delayed vaccination than children whose mothers had only primary education. [24,32,33] Caregivers who are educated are more likely to know the number of vaccine doses a child should receive and the age at which these doses should be received. [34] They may also know the importance of timely vaccination.…”
Section: Researchmentioning
confidence: 99%